The Mediating Role of Tax Compliance in the Relationship Between Carbon Tax and Environmental Performance: A Public Sector Study - Nedi Hendri; Fajar Gustiawaty Dewi; Khairudin Khairudin (The Indonesian Accounting Review, 2026)
This study examines the mediating role of tax compliance in the relationship between carbon tax and environmental performance in the public sector of Indonesia. The implementation of carbon tax, aimed at reducing greenhouse gas emissions, faces challenges in Indonesia due to low tax compliance, potentially undermining its effectiveness. A total of 318 participants from public sector organizations in Indonesia were selected using random sampling for this study. Data were collected through an online survey, designed to measure tax compliance, carbon tax, and environmental performance. The results indicate that tax compliance significantly mediates and moderates the relationship between carbon tax and environmental performance, highlighting the importance of improving tax compliance to enhance the effectiveness of carbon tax policies. This study provides empirical evidence on the critical role of tax compliance in maximizing the environmental benefits of carbon taxes in developing countries like Indonesia, where tax culture and enforcement systems are still evolving. The findings contribute to the literature on carbon taxation by emphasizing the need for fostering compliance to ensure the success of environmental tax policies.